Functional characterization of novel sesquiterpene synthases from Indian sandalwood, santalum album - Srivastava, Prabhakar Lal; Daramwar, Pankaj P.; Krithika, Ramakrishnan; Pandreka, Avinash; Shankar, S. Shiva; Thulasiram, Hirekodathakallu V. (Scientific Reports, 2015)
Indian Sandalwood, Santalum album L. is highly valued for its fragrant heartwood oil and is dominated by a blend of sesquiterpenes. Sesquiterpenes are formed through cyclization of farnesyl diphosphate (FPP), catalyzed by metal dependent terpene cyclases. This report describes the cloning and functional characterization of five genes, which encode two sesquisabinene synthases (SaSQS1, SaSQS2), bisabolene synthase (SaBS), santalene synthase (SaSS) and farnesyl diphosphate synthase (SaFDS) using the transcriptome sequencing of S. album. Using Illumina next generation sequencing, 33.32 million high quality raw reads were generated, which were assembled into 84,094 unigenes with an average length of 494.17 bp. Based on the transcriptome sequencing, five sesquiterpene synthases SaFDS, SaSQS1, SaSQS2, SaBS and SaSS involved in the biosynthesis of FPP, sesquisabinene, beta-bisabolene and santalenes, respectively, were cloned and functionally characterized. Novel sesquiterpene synthases (SaSQS1 and SaSQS2) were characterized as isoforms of sesquisabinene synthase with varying kinetic parameters and expression levels. Furthermore, the feasibility of microbial production of sesquisabinene from both the unigenes, SaSQS1 and SaSQS2 in non-optimized bacterial cell for the preparative scale production of sesquisabinene has been demonstrated. These results may pave the way for in vivo production of sandalwood sesquiterpenes in genetically tractable heterologous systems.